2015
DOI: 10.1007/s11060-015-1835-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcome of malignant giant cell tumor in the spine

Abstract: Malignant giant cell tumor (MGCT) in the spine is extremely rare and there is little published information regarding this subject in the literature. We attempted to correlate different treatment options and outcomes over time. A retrospective study of patients with spinal MGCT who were surgically treated in our center between 2006 and 2012 was performed. Overall, three surgical management strategies, including subtotal resection, piecemeal total resection, and total en bloc spondylectomy were applied. Postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…However, most of these tumours are benign, and only a small number of GCTs (1-2%) may undergo malignant transformation, leading to a poor prognosis. According to the previous reports, GCTs can transform into fibrosarcoma, osteosarcoma, malignant fibrous histiocytoma, undifferentiated high-grade pleomorphic sarcoma, and undifferentiated sarcoma [4,18,19]. GCTs of the bone appear as expansive lytic lesions with non-sclerosing, well-defined edges on radiography, whereas CT and MRI provide information on the extent of the bone, bone marrow, and surrounding soft tissue involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of these tumours are benign, and only a small number of GCTs (1-2%) may undergo malignant transformation, leading to a poor prognosis. According to the previous reports, GCTs can transform into fibrosarcoma, osteosarcoma, malignant fibrous histiocytoma, undifferentiated high-grade pleomorphic sarcoma, and undifferentiated sarcoma [4,18,19]. GCTs of the bone appear as expansive lytic lesions with non-sclerosing, well-defined edges on radiography, whereas CT and MRI provide information on the extent of the bone, bone marrow, and surrounding soft tissue involvement.…”
Section: Discussionmentioning
confidence: 99%
“…It typically originates in the metaphyseal ends of long bones and rarely in the spine [1][2][3]. Approximately 1.4-9.4% of GCTs occur in the vertebrae above the sacrum in patients aged 20-40 years, and they more commonly occur in women than in men [4]. Although GCT is predominantly considered as a benign lesion, it may change from an indolent and static tumour to a locally invasive lesion with extensive bone destruction, cortical breakthroughs, and soft tissue expansion [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "malignancy in GCTB" is used by the World Health Organization to describe such tumors, which show malignant potential and can completely transform into malignant tumors [25,26]. Currently, preoperative prediction and postoperative monitoring of GCTB patient prognosis are limited and mostly rely on patients' general information, radiological features, treatment history, and tumor pathological reports [1,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…En block excision is the optimal treatment option which is designed based on modern imaging techniques such as Magnetic Resonance Imaging (MRI) but may be extensive and disabling for the patient 10,27 . Yin et al in their series of 14 patients reported statistically significant lower local recurrence rates of malignant GCTs of the spine with total en bloc spondylectomy compared to subtotal or piecemeal total resections 28 . In the series of Kapoor SK et al, patients that developed malignant GCT and treated with en bloc excision, died within 5 months post diagnosis 29 .…”
mentioning
confidence: 96%